Comparative Evaluation of the Effect of Two Bonding Systems on the Shear Bond Strength of Orthodontic Brackets: An In Vitro Study - Ebrahimi, Hossein; Amiri, Zahra; Besharati Zadeh, Parisa; Salehi Vaziri, Abbas (Galen Medical Journal, 2025)
Background: Reliable bracket attachment is crucial for successful orthodontic treatment. Traditional bonding techniques utilize phosphoric acid to etch enamel by creating micromechanical retention, though this method can be technique-sensitive and time-consuming. Self-etch adhesives have been introduced to streamline this process by combining etching and priming into a single step. In this study we aimed at evaluating Transbond™ XT and Absolute2 bounding properties. Materials and Method: A total of sixteen premolars extracted recently were randomly allocated into two groups, each containing eight teeth. Metal brackets were bonded onto these teeth using either the etch-and-rinse adhesive Transbond™ XT or the self-etch adhesive Absolute2, according to the manufacturer’s guidelines. Following the bonding procedure, the specimens were immersed in water for 24 hours, then subjected to 1,000 thermal cycles between temperatures of 5°C and 55°C. Finally, shear bond strength was measured using a universal testing machine. Results: The mean Shear Bond Strength for Transbond™ XT was 16.03 ± 2.54 MPa, significantly higher than 0.14 ± 0.40 MPa for Absolute2 (P = 0.001). Most samples in the Absolute2 group failed before or after thermocycling, indicating insufficient bonding performance. Conclusion: The self-etch adhesive Absolute2 demonstrated inadequate bond strength to untreated enamel for orthodontic bracket bonding. Although self-etch adhesives simplify the procedure, enamel surface preparation or improved adhesive formulations are necessary for clinically reliable adhesion. Future studies should explore novel enamel conditioning methods and hydrolytically stable adhesives to enhance bonding durability.